The World Bank Policy for Projects on International Waterways : An Historical and Legal Analysis - Salman, Salman M. A. (World Bank, 2012)
This study deals with the evolution and context of the Bank policy for projects on international waterways. It starts with a brief description of how the Bank has faced the challenges stemming from such projects, and the different approaches deliberated by the Bank that led to the issuance of the first policy in 1956. The study then reviews the implementation experience of the policy and analyzes the principles and procedures, as well as the main features of each of the policies issued in 1956, 1965, and 1985 respectively. The principles of international water law prevailing at each stage of the policy issuance are examined and compared with those of the Bank policy. The study also discusses in detail the notification process: its basis, by whom, to whom, its content, different riparian's responses, and the exceptions to the notification requirement. It then analyzes how the Bank handles an objection from one or more of the riparian's to projects proposed for Bank financing. It also examines how the Bank has dealt with transboundary groundwater, as well as the linkages between the policy for projects on international waterways and the policies on disputed areas and environmental impact assessment. The conclusion provides an overview of the main findings of the study, and highlights some of the lessons drawn from the implementation experience of the policy.